Multi-Informant Assessment of ADHD Symptom-Related Impairments Among Children and Adolescents. Issue 5 (3rd September 2017) - Power, Thomas J.; Watkins, Marley W.; Anastopoulos, Arthur D.; Reid, Robert; Lambert, Mathew C.; DuPaul, George J.
Abstract : Existing methods of assessing attention-deficit/hyperactivity disorder (ADHD) are limited because they do not examine impairments in relation to symptoms of ADHD. This study investigated parent and teacher ratings of multiple domains of impairment, assessed in relation to the symptom dimensions of ADHD using the ADHD Rating Scale–5. Nationally representative samples of children rated by parents and teachers were recruited through commercial research firms. One sample included 2, 079 parents who rated one of their children of age 5 to 17 years. The second sample included 1, 070 teachers in grades K to 12 who rated 2 randomly selected students on their class rosters. Informants rated the extent to which each child displayed the 18 behaviors symptomatic of ADHD over the previous 6 months, as well as symptom-related impairments in the areas of family/teacher relationships, peer relationships, academics, behavior problems, homework, and self-esteem. Respondents were asked to complete the 6 impairment items after rating each of the Inattention and Hyperactivity/Impulsivity symptom items. For both informants a 6-factor model that combined impairment items across source of impairment was adequate and superior to a 2-factor structure based on source of impairment (i.e., impairment due to Inattention vs. Hyperactivity-Impulsivity). Impairment ratings were impacted by child demographic factors, but effect sizes were low. In contrast, impairment ratings were strongly related to ratings on the ADHD symptom dimensions. The study provides support for assessing 6 symptom-related domains of impairment but does not support differentiating whether Inattention or Hyperactivity-Impulsivity is the source of impairment.